The Role of the State in Industrial Relations: A Comment - Downie, Bryan (Relations industrielles / Industrial Relations, 1990)
In this paper, the author takes issues with comments by Sack and Lee that changes to British Columbia's labour legislation represent retrenchment in Canadian public policy in labour relations. In discussing the issue, he draws on the experience with a similar approach in Ontario.